2008
DOI: 10.1007/s00415-008-0680-6
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and social cognitive functioning in spinocerebellar ataxia

Abstract: The data support the hypothesis that the cerebellum is important for cognitive as well as motor activity. The pattern of overlap of domain impairments provides tentative preliminary evidence that there is a cerebellar contribution to aspects of memory and executive function and ToM, and that other domains depend more on neural system outside the cerebellum. The findings relating to ToM are relevant to the possibility of cerebellar involvement in autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
106
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(121 citation statements)
references
References 48 publications
11
106
1
2
Order By: Relevance
“…A previous study showed that a p38 inhibitor protects immature, vulnerable Purkinje neurons from neurotoxic stress [63]. Mice with Purkinje neuron degeneration have shown a spatial learning deficit in the water maze test [61,64,65]. These studies along with our current findings suggest that aberrant p38 activation/accumulation perturbs the movement-controlling function of Purkinje neurons.…”
Section: Discussionsupporting
confidence: 78%
“…A previous study showed that a p38 inhibitor protects immature, vulnerable Purkinje neurons from neurotoxic stress [63]. Mice with Purkinje neuron degeneration have shown a spatial learning deficit in the water maze test [61,64,65]. These studies along with our current findings suggest that aberrant p38 activation/accumulation perturbs the movement-controlling function of Purkinje neurons.…”
Section: Discussionsupporting
confidence: 78%
“…Alternatively, autistic action models may be tuned to both atypical (autistic) and typical movements. (Caillies, Hody, & Calmus, 2012;Eddy & Cavanna, 2015;Eddy & Rickards, 2015;Garrard, Martin, Giunti, & Cipolotti, 2008). Furthermore, our results may help to explain why children with Attention Deficit Hyperactivity Disorder (ADHD) and motor dysfunctions are rated as having more social interaction difficulties than children with ADHD only (Tervo, Azuma, Fogas, & Fiechtner, 2007).…”
Section: Discussionmentioning
confidence: 80%
“…A patient with cerebellar atrophy exhibited deficient RMET performance (Parente et al, 2013). Absence of deficits in mental state attribution but altered attribution of emotions to a character of a short story were reported in eight patients with SCA types 1, 2, and 7 (Sokolovsky et al, 2010), with the opposite picture in 15 patients with SCA 3 and 6 (Garrard et al, 2008). This dissociation could reflect distinct pathophysiology in SCA subtypes.…”
Section: Evidence From Cerebellar Degenerationmentioning
confidence: 90%